Bakti Sosial Kesehatan Donor Darah Dalam Rangka Memperingati Hut Kowal Ke 60 Tahun 2023 - Akhmad Syahbudin; Andri Ali Wardhana; Susi Herawati; Etik Purwanti (Akademi Maritim Nusantara Banjarmasin, 2023)
Abstract The concept of social service or social service is community service with an emphasis on personal, institutional and community. Blood donation is very important to help people who really need blood for transfusion. Therefore, many people want to donate their blood to people in need, but many people also those who don't donate blood may be due to insufficient body weight, and there are still many people who can't donate blood. many people who have donated blood forget to donate blood again, or don't donate blood regularly The technique or stage of implementing this community service is that after there is notification through an invitation from the Lanal to the Academic division about the Hut Kowal activity of blood donation social services, the lecturers and academic staff as well as the cadets of the Banjarmasin Archipelago Maritime Academy immediately participate in donating blood to the Banjarmasin Lanal, in Blood Donation Health Social Service in Commemoration of the 60th Anniversary of Kowal in 2023 with several lecturers and academy staff at the Banjarmasin Nusantara Maritime Academy. The results of this blood donation activity certainly add to the concern for the community by donating blood to those who need it immediately, and of course many more will be saved with the results of the blood donation. Keywords : Social service, Health, Blood Donation